Differentiated plant defense strategies: Herbivore community dynamics affect plant–herbivore interactions - Cindy Perkovich (Ecosphere, 2022)
Abstract Plant–herbivore interactions account for much of the biodiversity observed in an ecosystem. Plants may alter defense expression dependent on the specific herbivore present. Many studies focus on the optimization of these defenses against a single herbivore, but in an ecological context, there may be a myriad of herbivores at any given time. We designed a study to examine defenses employed by swamp white oak (Quercus bicolor) against insects and large mammals. We established six deer exclosures with trees located inside and outside each exclosure. Outside the exclosures, physical constraints only allow deer to feed up to a browseline on trees, whereas insects can potentially access all portions of the tree. Trees inside exclosures were only accessible to insect herbivores. Furthermore, insecticides were applied to half of the exclosures to create insect‐free (i.e., insecticide applied), deer‐free (i.e., inside exclosures), deer‐only (i.e., outside exclosures with insecticide), and herbivore‐free (i.e., inside exclosures with insecticide) environments. This design allowed us to analyze simultaneous defensive responses of individual trees to mammal and insect herbivores. We predicted that because insects represent a continuous threat, plants should invest in fixed concentrations of defenses (e.g., polyphenols, tannins, and condensed tannins), even when deer are absent. When deer are present, plants should increase investment in defenses in tissues that deer have access to. We found that plant defense strategies varied spatially on individual trees. When only insects were present, nutritional constituents (e.g., nitrogen and non‐structural carbohydrates) did not change but antinutritional constituents increased. Contrastingly, when deer were present, both nutritional and antinutritional constituents decreased. We found a decrease in insect functional group diversity when deer were present. Our findings suggest that plants may partition defense strategies depending on the most prominent herbivore pressure. However, changes in insect functional group diversity may result from either changes in plant defense strategy or intraspecific competition among multiple herbivores. Future studies should investigate patterns of chemical heterogeneity displayed by plants in response to diverse herbivore pressures.